Analysis and Design of Web-Based Project Management Information System Using Critical Path Method (CPM) Method on PT. Pakarti Tirtoagung - Felina Natalia Lie; Edy Edy (Fakultas Sains dan Teknologi-Universitas Buddhi Dharma, 2019)
PT. Pakarti Tirtoagung is one of the companies engaged in construction services in Indonesia, in the scope of gas and petroleum. To facilitate the company in carrying out the project implementation process and monitoring the progress of the project, a special computerized system is needed.Looking at the system that runs on the company, there is no specific system support, which has several obstacles, among others in making schedule project, errors in recording data and presenting project progress reports because project progress was not monitored, completion of projects that are not in accordance with time schedules, etc. Of the several obstacles encountered, it becomes an interesting discussion to looking for solutions that can minimize obstacles and even risks that will occur as a result of these constraints. For that it was made Analysis And Design Of Web-Based Project Management Information System Using Critical Path Method (CPM) Method On Pt. Pakarti Tirtoagung. Using the CPM method for help planning activities to project development. Based on the results of the questionnaire that was distributed to 10 (ten) respondents and after processing the results 58% of respondents felt agree and 38% strongly agree that the system can present information about the ongoing project, monitoring the project and presenting a project progress report .